2016
DOI: 10.1080/19420862.2016.1267087
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, behaviors and practices of community and hospital pharmacists towards biosimilar medicines: Results of a French web-based survey

Abstract: This study's aims were: 1) to extract a comprehensive overview of the knowledge, experience and opinions of both community pharmacists and hospital pharmacists regarding biosimilar medicines in France; and 2) to identify the perceived problems and solutions to promoting their prescription. A 2015 web-based survey was conducted by the Observatoire des Médicaments, des Dispositifs Médicaux et de l'Innovation Thérapeutique of Alsace. A total of 802 pharmacists responded to the survey. Many (536, 66.8%, [95% confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
46
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 33 publications
6
46
1
Order By: Relevance
“…Familiarity with the term biosimilar differed among HCP groups (Table 4 ). For instance, fewer community pharmacists (79.9%) were familiar with the term ‘biosimilar medicine’ than hospital pharmacists (95.4%), corroborating findings from a 2015 survey carried out in France, where a higher proportion of community pharmacists responded that they were not at all informed about biosimilars compared with hospital pharmacists [ 44 ]. A survey of HCPs conducted in Ireland the year before this current study (2016) found similar proportions of GPs and community pharmacists claimed they were familiar with the term biosimilar.…”
Section: Discussionsupporting
confidence: 66%
“…Familiarity with the term biosimilar differed among HCP groups (Table 4 ). For instance, fewer community pharmacists (79.9%) were familiar with the term ‘biosimilar medicine’ than hospital pharmacists (95.4%), corroborating findings from a 2015 survey carried out in France, where a higher proportion of community pharmacists responded that they were not at all informed about biosimilars compared with hospital pharmacists [ 44 ]. A survey of HCPs conducted in Ireland the year before this current study (2016) found similar proportions of GPs and community pharmacists claimed they were familiar with the term biosimilar.…”
Section: Discussionsupporting
confidence: 66%
“…Although healthcare professionals and patients appreciate that the pharmaceutical budget is finite and that biosimilars can help to sustain healthcare, their knowledge and experience with biosimilars tends to be limited [ 37 39 ]. In response to this, the European Commission has issued Q&A documents about biosimilars targeting healthcare professionals and patients [ 33 , 40 , 41 ], and also individual countries have started initiatives to educate stakeholders and help combat misconceptions and misinformation [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…The usage of biosimilars may allow facilities to save costs; in some countries and under certain circumstances biosimilars can be much cheaper than reference medicines and more patients could receive this modern therapy [ 23 25 ]. Community and hospital pharmacists (92%) from France indicated “Health care costs savings” as their motivation to promote the prescribing of biosimilars [ 26 ]. These arguments make biosimilar medicines very attractive, especially for Eastern European countries with limited healthcare budgets [ 27 ].…”
Section: Discussionmentioning
confidence: 99%